The Church in the context of corruption: A case of the Church of Christ in Zimbabwe - Mafohla, Shelton (HTS teologiese studies, 2024)
Corruption has caused serious dysfunction in most of the public institutions in Zimbabwe. The effectiveness of public institutions on providing meaningful services today hinges upon the capacity of the Church and other social institutions to combat corruption. Regrettably, corruption has infected and affected both the Church and the secular institutions. This theoretical qualitative study explores the potential of the Church of Christ in Zimbabwe (COCZ) in curbing corruption in Zimbabwe. It employs a combination of the Christological kenosis and Ubuntu or Hunhu as its theoretical lenses. The article argues that the Church has great potential to tackle corruption. The potential of the COCZ manifests in its organisation and public engagement. The restorative nature of the COCZ Restoration Movement (RM) magnifies scripture, the gospel of Christ (Christological kenosis) as a tool of conviction and behaviour change in public spaces to combat corruption. These unique attributes of the COCZ provide the rationale for choosing it as a case study in this article. The data were collected through the engagement with literature largely from the Zimbabwean scholars on the subject and the COCZ documents. The findings were that the COCZ can only unlock its potential if it is committed to taking a self-introspection and reconfigure itself in order to take a robust anti-corruption stance.Contribution: The study poses questions about the potential of the Church’s voice, through the case of the COCZ, in the context of corruption in Zimbabwe. It pushes for the Church to reclaim its authentic status in order to root out corruption and have relevance in the Zimbabwean communities’ lived experiences. Religion has always claimed higher ground in ethical and moral issues, but there is scanty literature on the COCZ’s role in combating corruption in Zimbabwe. The study maintains that the Church has a consequential opportunity to either drive the agenda to end corruption or lose relevance due to perceived complicit attitudes towards the same.